Global Citizenship in Technology Age from the Perspective of Social Sciences - Bulut, Birol; Cakmak, Zafer; Kara, Cihan (Elsevier Science Bv, 2013)
Technological changes are considered as a significant factor for the development of societies. This change has led to society's going beyond in addition to pervasion of value judgments pertaining to cultural, political and especially economic aspects and formation of internationally shared and valid structures. The development of technology, world's being smaller and increasing of its population rises the mutual dependency of us with the people whom we may never see in life. In this process, which also affects the educational systems, Global Citizenship conies to the fore in accordance with these developments as a model dealing with the problems of not only his own nation but also those of the whole humanity. In this study, which was carried out in literature review model, global citizen development ability of Social Sciences Instructional Programs through new communication media like social networks within the context of the relation between technology and society will be analyzed. (C) 2013 The Authors. Published by Elsevier Ltd.
13th International Educational Technology Conference -- OCT 30-NOV 01, 2014 -- Lisbon, PORTUGAL
Keywords: Social Networks; Global Citizenship; Information Technologies; Globalisation; Social Sciences Programs